2023
DOI: 10.1088/1741-2552/acb50d
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial ultrasound stimulation modulates the interhemispheric balance of excitability in human motor cortex

Abstract: Background: Low-intensity transcranial ultrasound stimulation (TUS) could induce both immediate and long-lasting neuromodulatory effects in human brains. Interhemispheric imbalance at prefrontal or motor cortices generally associates with various cognitive decline in aging and mental disorders. However, whether TUS could modulate the interhemispheric balance of excitability in human brain remains unknown. Objective: This study aims to explore whether repetitive TUS (rTUS) intervention can modulate the interh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…TMS-induced MEP). In a series of work combining offline TUS and TMS in humans, MEP amplitudes were amplified by repetitive low PRF offline TUS (PRF range 5-100 Hz, see Table 1 for details of the protocols) [22][23][24]. Facilitatory effects were still present 30 minutes post-sonication in one study [24], confirming the duration of offline TUS effects on neural transmission.…”
Section: Modulation Of Evoked Responsementioning
confidence: 76%
See 1 more Smart Citation
“…TMS-induced MEP). In a series of work combining offline TUS and TMS in humans, MEP amplitudes were amplified by repetitive low PRF offline TUS (PRF range 5-100 Hz, see Table 1 for details of the protocols) [22][23][24]. Facilitatory effects were still present 30 minutes post-sonication in one study [24], confirming the duration of offline TUS effects on neural transmission.…”
Section: Modulation Of Evoked Responsementioning
confidence: 76%
“…In a series of work combining offline TUS and TMS in humans, MEP amplitudes were amplified by repetitive low PRF offline TUS (PRF range 5-100 Hz, see Table 1 for details of the protocols) [22][23][24]. Facilitatory effects were still present 30 minutes post-sonication in one study [24], confirming the duration of offline TUS effects on neural transmission. Contrasting with these results, Zhang et al [11] found excitatory effects in the form of decreased intracortical inhibition produced by a high PRF protocol (2000Hz) and inhibitory effectsreduced MEP amplitudes, increased intracortical inhibition and decreased intracortical facilitationwith a lower PRF protocol (50Hz).…”
Section: Modulation Of Evoked Responsementioning
confidence: 76%
“…Several studies have shown that inhibitory NIBS protocols increase the excitability of the contralateral M1 (Chen et al., 1997; Gilio et al., 2003; Huang et al., 2005; Suppa et al., 2008; Takamatsu et al., 2021) and excitatory NIBS protocols decrease the excitability of the contralateral M1 (Suppa et al., 2008). One group found that 15 min of repetitive TUS increased ipsilateral MEP amplitudes and decreased contralateral MEP amplitudes (Ren et al., 2023). Consistent with these findings, we found that left M1 tbTUS increased right M1 excitability.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Zhang et al (2021) [24], tFUS administered for 15 min increased MEP amplitudes for ~30 min and improved inhibitory control function in the tasks conducted immediately after tFUS. Using the same sonication parameters, Ren et al (2023) [25] reported that tFUS to the left M1 increased the ipsilateral M1 excitability for ~30 min while decreased the contralateral M1 excitability for ~15 min, as assessed by TMS-induced MEP amplitudes, along with improved cognitive performance. In 2022, with a tFUS transducer, and no interference between tFUS and TMS was reported.…”
Section: Nrmentioning
confidence: 99%
“…In another study, Samuel et al (2023) [71] delivered in stroke treatments, utilizing NIBS such as repetitive TMS (rTMS) and transcranial direct current stimulation (tDCS) to normalize interhemispheric imbalances in stroke patients. In the case of tFUS, although not a study involving stroke patients, Ren et al (2023) [25] (listed in Table 2) observed that the excitatory effects of tFUS stimulation on the unilateral M1 in humans were accompanied by decreased excitability in the contralateral M1, suggesting the potential of tFUS in clinical interventions such as a rebalancing modality of the interhemispheric imbalances in stroke.…”
Section: Alzheimer's Disease (Ad) and Parkinson's Diseasementioning
confidence: 99%